Exploring the integration of CAT into translation programmes at Saudi universities - Talal Musaed Alghizzi; Muhammad M. Abdel Latif (International Journal of Linguistics, Literature and Translation, 2025)
Important issues are yet to be explored regarding computer-assisted translation (CAT) integration into translator training programmes in the Saudi context. In this study, we sought to explore the realities of CAT integration into translator training programmes at Saudi universities by examining the characteristics of the CAT courses offered, trainers’ perspectives on using CAT activities in non-CAT translation courses, and the challenges encountered. We tried to profile these issues through reviewing translation programme study plans and CAT course descriptions, and collecting interview data from eight translation faculty members working at five Saudi universities. The results indicate the lack of CAT courses in a considerable number of undergraduate translation programmes. Besides, the available CAT courses in both the undergraduate and postgraduate translation programmes lack the sufficient training or a practical part. The interviewed faculty members were found unwilling to integrate CAT-based activities into non-CAT translation courses. Their reported obstacles to the effective CAT integration include the limited time, students’ non-responsiveness, and the unavailability of required applications. These results indicate the need for reforming CAT teaching practices and integrating CAT more effectively into translator training programmes.